Options for self-reliant resurgence : CPD's rapid assessment of flood 2004 - Centre for Policy Dialogue (Bangladesh) (Dhaka : Centre for Policy Dialogue : University Press, 2005)
With reference to Bangladesh.
Includes bibliographical references (p. [71]).
Keywords: Floods -- Bangladesh; Food supply -- Bangladesh; Food relief -- Bangladesh; Disaster relief -- Bangladesh